Resilience of dermis resident macrophages to inflammatory challenges - Sang Hun Lee; David L. Sacks (Experimental and Molecular Medicine)
Abstract The skin serves as a complex barrier organ populated by tissue-resident macrophages (TRMs), which play critical roles in defense, homeostasis, and tissue repair. This review examines the functions of dermis resident TRMs in different inflammatory settings, their embryonic origins, and their long-term self-renewal capabilities. We highlight the M2-like phenotype of dermal TRMs and their specialized functions in perivascular and perineuronal niches. Their interactions with type 2 immune cells, autocrine cytokines such as IL-10, and their phagocytic clearance of apoptotic cells have been explored as mechanisms for M2-like dermal TRM self-maintenance and function. In conclusion, we address the need to bridge murine models with human studies, with the possibility of targeting TRMs to promote skin immunity or restrain cutaneous pathology.